The Art of the Editorial - van Teijlingen, Edwin; Hundley, Vanora; Sathian, Brijesh; Simkhada, Padam; Robinson, Jared; Banerjee, Indrajit (Nepal Journal of Epidemiology, 2022)
Many traditional scientific journals carry an editorial at the start of each issue or perhaps in most issues. The more recently established online journals seemed to have discontinued this tradition, for example there is no editorial in Sociological Research Online or many of the online journals in the BMC stable, such as BMC Pregnancy & Childbirth or BMC Public Health. Over the past two decades we have published close to fifty editorials between us. We would like to highlight some of their specific features to offer advice and encouragement to would-be editorial writers, and, more generally, promote the writing and publishing of editorials. This paper includes an overview of the eight most recent editorials, all focusing on the hot topic of COVID-19, published in this scientific journal.